Survival analysis - Kartsonaki, C (Elsevier, 2016)
Survival analysis is the analysis of data involving times to some event of interest. The distinguishing features of survival, or time-to-event, data and the objectives of survival analysis are described. Some fundamental concepts of survival analysis are introduced and commonly used methods of analysis are described.